(untitled) - Kurosaki, Makoto (Tokyo, 2017)
The Cold War has ended and China has overtaken Japan as Number Two. The digital revolution has come and IoT is changing everything. And yet Japan remains near the top as the third richest economy in the world despite the fallout from the scandals and disappointing performance from some of Japan's former giants. How can this be? What is the true source of strength of the Japanese economy? Who are the real little giants who continue to sustain Japan? Read about 24 amazing Japanese SMEs that have left footprints way beyond their corporate size.
Keywords: Small business,Doanh nghiệp nhỏ; Management,Quản lý